User acceptance in a changing context: why some product-service systems do not suffer acceptance problems. (1st January 2014) - Schotman, Hendrikus; Ludden, Geke Dina Simone
The Western world is increasingly moving towards a service-oriented economy. The concept of product-service systems (PSSs) can help to deal with this transition. However, users and businesses are generally required to change their normal way of behaving to adhere to a PSS and this often acts as a barrier for successful implementation. This lack of required behavioural change often results in poor user acceptance and many PSS initiatives fail after successful pilot projects. Various measures are put forward to improve acceptance, but not all measures focus on changing user habits. This paper argues that PSSs can be more powerful in gaining user acceptance when they are designed to address lost habits, owing to unwillingly changed behaviour.